2017
DOI: 10.1186/s12974-016-0787-0
|View full text |Cite
|
Sign up to set email alerts
|

Absence of system xc − on immune cells invading the central nervous system alleviates experimental autoimmune encephalitis

Abstract: BackgroundMultiple sclerosis (MS) is an autoimmune demyelinating disease that affects the central nervous system (CNS), leading to neurodegeneration and chronic disability. Accumulating evidence points to a key role for neuroinflammation, oxidative stress, and excitotoxicity in this degenerative process. System xc − or the cystine/glutamate antiporter could tie these pathological mechanisms together: its activity is enhanced by reactive oxygen species and inflammatory stimuli, and its enhancement might lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 93 publications
0
19
1
Order By: Relevance
“…Our discovery that xCT is expendable for T cell proliferation and function in vivo unexpectedly yielded results that clearly conflicted with those obtained ex vivo. Although others have reported that either systemic or immune cell-specific disruption of xCT can alleviate T cell-driven EAE (24, 25), we have found that systemic or T cell-specific knockout of xCT does not disrupt the antitumor T cell response. While we focused on T cell proliferation and the adaptive immune response against tumors, it has also been reported that xCT-deficient mice exhibit enhanced expression of IL-1β and TNF-α at the site of 3-methylcholanthrene injection, which was attributed to increased death of macrophages and neutrophils (34).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Our discovery that xCT is expendable for T cell proliferation and function in vivo unexpectedly yielded results that clearly conflicted with those obtained ex vivo. Although others have reported that either systemic or immune cell-specific disruption of xCT can alleviate T cell-driven EAE (24, 25), we have found that systemic or T cell-specific knockout of xCT does not disrupt the antitumor T cell response. While we focused on T cell proliferation and the adaptive immune response against tumors, it has also been reported that xCT-deficient mice exhibit enhanced expression of IL-1β and TNF-α at the site of 3-methylcholanthrene injection, which was attributed to increased death of macrophages and neutrophils (34).…”
Section: Discussioncontrasting
confidence: 92%
“…If this model is correct, then systemic inhibition of xCT may negatively impact T cell function. Although xCT has been implicated in promoting the pathophysiology of experimental autoimmune encephalomyelitis (EAE), a T cell-driven form of autoimmunity (24, 25), the requirement for xCT in supporting T cell proliferation or antitumor immunity has not been evaluated in vivo.…”
mentioning
confidence: 99%
“…Mice lacking xCT, the major component of system x c − are viable [32] and are even protected against 6-hydroxydopamine-induced toxicity [33] probably by a significant decrease in striatal extracellular glutamate levels [34]. The specific cell type that upregulates xCT also seems to be important; while a complete knockout of xCT had no effect on the severity of experimental autoimmune encephalomyelitis, cell-type specific knockout only in immune cells alleviated disease severity [35].…”
Section: Relevance Of Oxytosis In Vivomentioning
confidence: 99%
“…In 2011, Pampliega and colleagues reported that the light chain of the heterodimeric xc- transmembrane protein (known as xCT) responsible for its transporter activity is upregulated in the spinal cord of mice and rats with experimental autoimmune encephalomyelitis (EAE), the most widely characterized rodent model of MS, as well as human MS postmortem tissue [ 6 ]. A recent study by Merckx and colleagues suggests that it is the peripheral immune cells expressing xc-, known to infiltrate the CNS in MS, rather than the resident immune cells that directly contribute to glutamate release and excitotoxicity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%